The acute effects of light on murine sleep during the dark phase: importance of melanopsin for maintenance of light‐induced sleep. Issue 11 (20th March 2013) - Muindi, Fanuel; Zeitzer, Jamie M.; Colas, Damien; Heller, H. Craig
Abstract Light exerts a direct effect on sleep and wakefulness in nocturnal and diurnal animals, with a light pulse during the dark phase suppressing locomotor activity and promoting sleep in the former. In the present study, we investigated this direct effect of light on various sleep parameters by exposing mice to a broad range of illuminances (0.2–200 μW/cm2; equivalent to 1–1000 lux) for 1 h during the dark phase (zeitgeber time 13–14). Fitting the data with a three‐parameter log model indicated that ∼0.1 μW/cm2 can generate half the sleep response observed at 200 μW/cm2. We observed decreases in total sleep time during the 1 h following the end of the light pulse. Light reduced the latency to sleep from 30 min in darkness (baseline) to 10 min at the highest intensity, although this effect was invariant across the light intensities used. We then assessed the role of melanopsin during the rapid transition from wakefulness to sleep at the onset of a light pulse and the maintenance of sleep with a 6‐h 20 μW/cm2 light pulse. Even though the melanopsin knockout mice had robust induction of sleep ( 35 min) during the first hour of the pulse, it was not maintained. Total sleep decreased by almost 65% by the third hour in comparison with the first hour of the pulse in mice lacking melanopsin, whereas only an 8% decrease was observed in wild‐type mice. Collectively, our findings highlight the selective effects of light on murine sleep, and suggest that melanopsin‐based photoreception is primarily involved in sustaining light‐induced sleep.